2016
DOI: 10.1007/s40266-016-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Polypharmacy from the Perspectives of General Practitioners and Older Patients: A Synthesis of Qualitative Studies

Abstract: Complex medication regimens and uncertainties in decision making are challenges for both GPs and patients. For patients, symptom experiences with medicines, relationship with their prescriber, and fragmented care are at the forefront; for GPs, it is the decision-making responsibility in the context of unsuitable guidelines, time constraints, and deficient multidisciplinary co-operation. Heuristics such as prioritizing and individualizing treatments and relaxation of guidelines emerged. These strategies require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 60 publications
8
130
0
1
Order By: Relevance
“…In Västerbotten, around 11% of older people ≥75 years of age had excessive polypharmacy (10 or more prescribed medications) and it was more common among women compared with men during 2013 [25,26]. Taken together and similar to other experiences, it is very likely that our findings reflect concerns about the usage of drugs as well as side effects and polypharmacy [27]. Patients with adverse drug reactions were likely classified under their experienced symptoms as reason for contact, rather than drug-related questions, unless they themselves where suspicious and asked about adverse drug reactions.…”
Section: Discussionsupporting
confidence: 52%
“…In Västerbotten, around 11% of older people ≥75 years of age had excessive polypharmacy (10 or more prescribed medications) and it was more common among women compared with men during 2013 [25,26]. Taken together and similar to other experiences, it is very likely that our findings reflect concerns about the usage of drugs as well as side effects and polypharmacy [27]. Patients with adverse drug reactions were likely classified under their experienced symptoms as reason for contact, rather than drug-related questions, unless they themselves where suspicious and asked about adverse drug reactions.…”
Section: Discussionsupporting
confidence: 52%
“…Having multiple clinicians caring for one patient and limited communication between physicians were identified as factors that inhibited deprescribing and increased the risk of polypharmacy [11][12][13]15. This may indicate that deprescribing does not happen as often as it should be in practice because of barriers such as fear of adverse effects, patients and/ or caregiver beliefs, and medications initially prescribed by another physician.Our results reinforce early findings about barriers preventing physicians from deprescribing, such as the fear of the recurrence of previous conditions for which a medication may have been initially prescribed.…”
mentioning
confidence: 99%
“…Even though most physicians felt confident about deprescribing in their elderly patients, their responses to questions about attitudes and barriers showed that many circumstances affected their ability to effectively engage in the deprescribing process. Other studies found that complexity at the prescriber level (especially the fragmentation of care and involvement of multiple prescribers) can hinder deprescribing among elderly patients [11][12][13]. 11-17 A majority of physicians reported comfort in deprescribing preventive medication, but fewer were comfortable with deprescribing guideline-recommended therapeutic medications in patients with poor life expectancy.…”
mentioning
confidence: 99%
“…The coordination of medications and the interactions between them is commonly flagged as a core burden (56,93,129,195,197,205,206,211). Multiple medications (Noel et al (93) identified that some patients take up to 27 medications) are associated with confusion, a sense of being overwhelmed (93,111,129,195,209,211), or a feeling of "resentfulness" at the level of dependence (93).…”
Section: Medication Burdenmentioning
confidence: 99%
“…As a result, clinicians, like their patients, experience high levels of uncertainty in the presence of multiple conditions due to limited evidence on how conditions, medications and other treatments will interact or conflict (19,73,79,123,211,224,229,230 In summary, the preceding sections of this chapter have endeavoured to navigate the experience of patients and clinicians living with and managing multiple chronic conditions. The discussion has identified that patients and GPs experience numerous barriers associated with the management of multiple chronic conditions, but at the patient level, the process of prioritising and re-prioritising emerges as a potential response to address some of these barriers.…”
Section: Chronic Disease: the Clinician Experiencementioning
confidence: 99%